2005
DOI: 10.1177/1536867x0500500206
|View full text |Cite
|
Sign up to set email alerts
|

Data Inspection using Biplots

Abstract: Biplots display interunit distances, as well as variances and correlations of variables of large datasets. They can be used as a tool to reveal clustering, multicollinearity, and multivariate outliers, and to guide the interpretation of principal component analyses (PCA). This article describes the uses of biplots and its implementation in Stata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 11 publications
0
44
0
3
Order By: Relevance
“…An angle of 0 or 180⁰ reflects a correlation of 1 or −1, respectively (Kohler and Luniak, 2005). The superimposition of KSB strains and K-solublization in various stressful growth environments showed that Pseudomonas sabulinigri BHU19 and Pseudomonas azotoformans BHU21 showed significantly higher correlation with all major parameters (Tables 8 and 9).…”
Section: Multivariate Analysismentioning
confidence: 99%
“…An angle of 0 or 180⁰ reflects a correlation of 1 or −1, respectively (Kohler and Luniak, 2005). The superimposition of KSB strains and K-solublization in various stressful growth environments showed that Pseudomonas sabulinigri BHU19 and Pseudomonas azotoformans BHU21 showed significantly higher correlation with all major parameters (Tables 8 and 9).…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Finalmente, el análisis gráfico es sumamente útil para la interpretación del ACP. El biplot es un gráfico de k ejes (cada uno representa un componente principal) y que permiten detectar estructuras de clustering, multicolinealidad y datos atípicos a nivel multivariado en un conjunto de observaciones (Kohler & Luniak 2005). Por lo general, el biplot es una representación cartesiana de dos o tres dimensiones, es decir, se espera que dos o tres componentes expliquen en conjunto la mayor proporción de la variabilidad de los datos.…”
Section: Apéndice a Análisis De Componentes Principalesunclassified
“…PCA biplots represent projections of multivariate datasets that exhibit the variance-covariance (or correlational) structure of the variables, the values of observations related to those variables, and the distances between observations in a multidimensional space for a given data matrix (Kohler and Luniak 2005). The PCs are arranged in the order of decreasing variance.…”
Section: Principal Component Analysismentioning
confidence: 99%